To play or not to play? A thematic analysis exploring the impact of adult-play on Primary teachers in Hong Kong. (Journal of Play in Adulthood)
This study aimed to evaluate the subjective experience of a play-based intervention on a sample of primary school teachers in Hong Kong. Semi-structured interviews and reflective journals provided data for qualitative analysis. Reflexive thematic analysis was applied to establish commonalities and/ or disparities in the participants’ lived experiences. Three superordinate themes were identified; perception, psychological impact and possibilities. Participants reported positive psychological responses and enhanced collegial relationships. Some showed awareness of personal and professional growth. Participants’ well-being was not measured or evaluated as part of this study. However, results suggest that play-based interventions for teachers may contribute to increased well-being through play's permeating effects. This may interest school leaders, well-being consultants, and positive psychology professionals administering school-based interventions to improve well-being and teacher collaboration. Adult play, an understudied area within positive psychology, lacks data and empirical research. Therefore, this study contributes to this emerging and exciting field.